Pengaruh Gaya Kepemimpinan, Pendidikan dan Pelatihan, dan Lingkungan Kerja terhadap Kinerja Anggota Satuan Polisi Pamong Praja di Kabupaten Kotawaringin Timur - Arson; Bambang Mantikei; Usup Riassy Christa (Program Pascasarjana Universitas Palangka Raya dan (and) Ikatan Ahli Teknik Penyehatan dan Teknik Lingkungan Indonesia (IATPI), 2020)
The purpose of this study were to analyze the influence of leadership style, education and training, and working environment on performance of civil service police member (Satuan Polisi Pamong Praja/Satpol PP) in Kotawaringin Timur regency. A descriptive quantitative analysis was used to examine 88 personnel of the unit. The results indicate that, first, leadership style has no definite and significant effect on personnel‘ performance. Secondly, education and training have a significant effect on members‘ performance. Lastly, a pleasant working environment has positively affected the personals‘ performance. This research suggests strengthening a positive leadership model that can make the work atmosphere more comfortable, increasing employees‘ engaged and enthusiastic so that they are willing to put their potency in order to complete the task.